Eccentric Exercise Versus Eccentric Exercise and Soft Tissue Treatment (Astym) in the Management of Insertional Achilles Tendinopathy: A Randomized Controlled Trial - McCormack, Joshua R. (Sports Health, 2016)
BACKGROUND: Eccentric exercise is commonly used in the management of Achilles tendinopathy (AT) but its effectiveness for insertional AT has been questioned. Soft tissue treatment (Astym) combined with eccentric exercise could result in better outcomes than eccentric exercise alone. HYPOTHESIS: Soft tissue treatment (Astym) plus eccentric exercise will be more effective than eccentric exercise alone for subjects with insertional AT. STUDY DESIGN: Prospective randomized controlled trial. LEVEL OF EVIDENCE: Level 2. METHODS: Sixteen subjects were randomly assigned to either a soft tissue treatment (Astym) and eccentric exercise group or an eccentric exercise–only group. Intervention was completed over a 12-week period, with outcomes assessed at baseline, 4, 8, 12, 26, and 52 weeks. Outcomes included the Victorian Institute of Sport Assessment Achilles-Specific Questionnaire (VISA-A), the numeric pain rating scale (NPRS), and the global rating of change (GROC). RESULTS: Significantly greater improvements on the VISA-A were noted in the soft tissue treatment (Astym) group over the 12-week intervention period, and these differences were maintained at the 26- and 52-week follow-ups. Both groups experienced a similar statistically significant improvement in pain over the short and long term. A significantly greater number of subjects in the soft tissue treatment (Astym) group achieved a successful outcome at 12 weeks. CONCLUSION: Soft tissue treatment (Astym) plus eccentric exercise was more effective than eccentric exercise only at improving function during both short- and long-term follow-up periods. CLINICAL RELEVANCE: Soft tissue treatment (Astym) plus eccentric exercise appears to be a beneficial treatment program that clinicians should consider incorporating into the management of their patients with insertional AT.